TECHNICAL AND ECONOMICAL EVALUATION FOR ELECTRICAL SUBMERCIBLE PUMP OPTIMAZATION USING VARIETY OF STAGES AND FREQUENCIES AT THE “INTB-12” WELL IN THE WIDURI FIELD - Batubara, Reinhard Fredrik; Suranto, Suranto; Ratnaningsih, Dyah Rini (Journal TECHNO, 2021)
Based on the analysis and calculations from daily production reports, there was a decrease in oil production of about 500 barrels of oil per year in the Widuri Field. The output of fluid produced occurred since drilling activities, completion of wells and production. In addition, other problems arise related to production optimization, namely excessive use of electrical energy in electrical submersible pumps, artificial lifts used to produce hydrocarbon fluids in Widuri Field with limited electrical energy capacity. ESP optimization can use VSD, because the ESP pump motor is an induction motor, where the speed is very proportional to the electric power supply. By adjusting the frequency of the ESP motor on the VSD, of course, you will be able to control the operation of the ESP in a wider range of capacity, head, and efficiency, so that you can determine the price of the desired optimum production rate based on 70% - 80% of Qmax. The optimization will be carried out in this research is to replace the ESP type with the number of stages and the number of new frequencies as well as calculating the lifting cost ratio. The purpose and objective of writing this research is to evaluate the volumetric efficiency of the pump that is being installed in the well so that optimization can be done in the study well by doing various ways and calculating the economic of each pump, that it gets the most economical lifting cost price. The method of this paper is the variation of stages and frequencies to get how much% volumetric efficiency, the Pump Discharge (P2) and Pump Intake (P3) methods to optimize the pump in the study well and Oil Lifting Cost for its economy. The conclusion is that you can determine which ESP pump to use based on the oil lifting cost.